THE IMPACT OF THE USE OF RESEARCH-BASED BIODIVERSITY E-LEARNING ON THE DEVELOPMENT OF CONSERVATION LITERACY SKILLS IN MIDDLE SCHOOL STUDENTS IN GRADE VII - Prasetyo, Tegar Bayu; Leksono, Suroso Mukti; Kurniasih, Septi; Nestiadi, Adi (Universitas Pakuan, 2025)
The low ability of conservation literacy is the main problem currently faced, one of which is caused by an inappropriate learning system. Therefore, contextualized teaching materials are needed to solve this problem. The purpose of this study is to describe whether or not there is an effect of using e-LKPD based on research results on the topic of biodiversity on students' conservation literacy skills, cognitive, affective and psychomotor aspects. This study uses a type of quantitative research with the method used is quasi-experimental with nonequivalent control group design. The sample in this study was taken using the slovin method. The data analysis technique used was T-test. In the research, the experimental class used e-LKPD and the control class used e-LKPD developed by the subject teacher. The results shown that: (1) there is a significant effect on conservation literacy of cognitive indicators (Sig. 0.000), (2) there is a significant effect on conservation literacy of affective indicators (Sig. 0.000), (3) there is a significant effect on conservation literacy of psychomotor indicators (Sig. 0.000). The conclusion of the study is that there is an effect of e-LKPD based on research results on biodiversity on students' conservation literacy skills.